APLIKASI KONSEP PENDIDIKAN ISLAM INTEGRATIF PADA TRADISI KENDUREN - Fifi Nur Rokhmah (CV. Amerta Media, 2017)
Tradition is a belief with symbolic meaning. It has become a routinely habit that is done by the society at certain times. Tradition of being an integral part of a civilized society. Indonesia as a country with diverse cultures has a lot of meaningful tradition. One tradition is mostly done by the society of Indonesia, especially Java society is kenduren which sometimes referred to as selametan. Kenduren is a form of tradition that integrates some of the Islamic teachings into a single unit. Through kenduren, society can apply some of the Islamic values at one time. This tradition experienced pros and cons among the society of Indonesia. Cons society considers kenduren is heresy (bid’ah) and is shirk (syirik). For the pros society, kenduren is considered to have many benefits and is a positive thing, and in accordance with Islamic teaching and should be well preserved.Key Words: Tradition, Kenduren, Integrative, and Islamic Teaching